2012
DOI: 10.1186/1743-7075-9-23
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary inulin, statin, and their co-treatment on hyperlipidemia, hepatic steatosis and changes in drug-metabolizing enzymes in rats fed a high-fat and high-sucrose diet

Abstract: BackgroundRats fed a high-fat and high-sucrose (HF) diet develop hepatic steatosis and hyperlipidemia. There are several reports that a change in nutritional status affects hepatic levels of drug-metabolizing enzymes. Synthetic inulin is a dietary component that completely evades glucide digestion. Supplementing a HF diet with inulin ameliorates hypertriglycemia and hepatic steatosis, but not hypercholesterolemia. This study aimed at distinguishing the effects of synthetic inulin and 3-hydroxy-3-methylglutaryl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…It is also not clear, whether under special dietary conditions or simultaneously applied with other agents, such as xenobiotics, butyrate may modify the liver enzymes of biotransformation. For example, dietary supplementation of inulin, a precursor of colonic butyrate production, in rats, suffering from high-fat-diet-induced hyperlipidaemia and hepatic steatosis, counteracted the decrease in the expression and activity of hepatic CYP1A1/2 and CYP2E1 enzymes [28]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also not clear, whether under special dietary conditions or simultaneously applied with other agents, such as xenobiotics, butyrate may modify the liver enzymes of biotransformation. For example, dietary supplementation of inulin, a precursor of colonic butyrate production, in rats, suffering from high-fat-diet-induced hyperlipidaemia and hepatic steatosis, counteracted the decrease in the expression and activity of hepatic CYP1A1/2 and CYP2E1 enzymes [28]. …”
Section: Resultsmentioning
confidence: 99%
“…For instance, the HDAC inhibitor trichostatin A was shown to influence the in vitro expression of the CYP3A subfamily [27]. Alimentary added inulin, which is fermented by the colonic bacteria to SCFA, alleviates the reduction in the expression and activity of hepatic CYP1A1/2 and CYP2E1 enzymes in rats kept on a high-fat diet [28], possibly due to the epigenetic effects of the absorbed SCFA. On the basis of these findings, the enteral microbiome-produced or the orally added butyrate may also alter the activity of CYP enzymes, have an impact on hepatic detoxification capacity and drug metabolism, defined as possible pharmacoepigenetic influences.…”
Section: Introductionmentioning
confidence: 99%
“…Fructan is a non-digestible fiber with health benefits [23-25]. It selectively stimulates the growth and/or activity of some beneficial bacteria in the colon and represses the growth of pathogens [8].…”
Section: Discussionmentioning
confidence: 99%
“…An elevation in the expression of Cyp3a was also observed in a rat model of alcohol-and high fat-induced liver injury [54]. In contrast, in patients with severe stages of NAFLD, a tendency for CYP3A4 expression to decrease with the progression of NAFLD was noted [24]. In addition, CYP3A4 activity in the patients with cirrhosis was significantly reduced, whereas the levels in patients with obstructive jaundice were unchanged [55].…”
Section: Genes Accession No Forward Primer Reverse Primer Probementioning
confidence: 90%
“…The concept of dietary imbalance, such as excessive consumption of high saturated fat and high fructose, has been revealed to be a contributing factor to the increased visceral adiposity and lipids associated with metabolic syndromes, which may subsequently progress into NAFLD [23,24]. Extensive studies have indicated that liver diseases cause the modifications in the expression of CYPs [25][26][27].…”
Section: Genes Accession No Forward Primer Reverse Primer Probementioning
confidence: 98%